Christine Ladd-Franklin: Pragmatist Feminist. - Agler, David W.; Durmuş, Deniz (Transactions of the Charles S. Peirce Society)
Before the early 1990s, accounts of classical American philosophy paid relatively little attention to the work and intellectual contributions of women philosophers. However, as early as 1991, a number of contemporary feminist philosophers and historians began to devote more focused attention to women philosophers whose intellectual achievements had been marginalized or forgotten. One woman philosopher whose contributions have still gone unnoticed is that of American logician, mathematician, and color theorist Christine Ladd-Franklin. This paper argues that Ladd-Franklin's feminist efforts to increase the opportunities for women in professional academia were influenced not only by her work as a woman scientist and her reading of feminist literature but also by her understanding of pragmatism and her interaction with Charles Peirce. Specifically, Ladd-Franklin's arguments to increase academic research positions for women and her criticisms of male-only scientific societies (i) point out how discrimination on the basis of gender violates Peirce's first rule of reason that one ought not block the road to inquiry and (ii) expose the unscientific nature of gender discrimination by contrasting the pragmatic meaning of acquiring a doctorate with the institutional practice of barring women from making intellectual contributions by denying them professorial positions.